(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To synthesize contemporary evidence on the benefits and risks of integrating traditional East Asian medicine (e.g., acupuncture, classical herbal formulas such as Simiao Decoction, Tripterygium wilfordii extracts) with standard Western therapies in gout and rheumatoid arthritis (RA). Method: We narratively reviewed major international guidelines for gout and RA and recent systematic reviews and randomized trials on acupuncture and herbal therapies. Sources were identified from PubMed/PMC and Cochrane; eligibility focused on adult gout or RA, integrative regimens versus Western care alone, and clinically relevant outcomes. Results: Western guidelines emphasize urate‑lowering therapy, colchicine/NSAIDs/corticosteroids for gout, and treat‑to‑target DMARD strategies for RA. Evidence for integrative approaches is mixed. In RA, a randomized trial showed Tripterygium wilfordii extract outperformed sulfasalazine for ACR responses but carries important toxicity warnings requiring careful risk-benefit assessment. Acupuncture for RA shows heterogeneous methods with inconsistent benefits across reviews, with some summaries indicating minimal impact on pain or disease activity, while others report improvements in symptoms and function. In gout, classical formulas (e.g., Simiao) demonstrate anti‑inflammatory and urate‑lowering mechanisms in preclinical models and small clinical studies; recent reviews suggest potential symptom relief and safety when used adjunctively, but study quality varies. Conclusions: Integrative regimens may offer symptomatic relief for some patients when layered onto guideline‑based Western care, provided safety (notably with Tripterygium wilfordii) and herb-drug interactions are actively managed. Current evidence supports shared decision‑making and selective, closely monitored use rather than routine adoption. High‑quality, sham‑controlled and add‑on randomized trials with standardized outcomes are still needed.